Stress, anxiety, and depression in times of COVID-19: Gender, individual quarantine, pandemic duration and employment - Levy, Inna (Frontiers in Public Health, 2022)
Objectives This study explores the inter-relationship between emotional distress in adults and gender, quarantine experiences, pandemic duration, and employment. Methods An online cross-sectional online survey comprised 943 Israelis. The link to the survey was distributed via different personal and academic social networking sites (e.g., Facebook, WhatsApp, and Twitter). The survey was administered using the online survey portal Google Forms. Participants addressed questions about their socio-demographic characteristics (e.g., gender, age, family status, employment, and quarantine experiences) and ranked their levels of stress, anxiety, and depression using the Hebrew version of the Depression, Anxiety and Stress Scale-DASS-21. Results The majority of the respondents (72%) were women, 39% experienced quarantine, and 55% were unemployed. About 42% experienced a short-term pandemic (one lockdown), and the rest experienced a continuous pandemic (two lockdowns). The MANCOVA results, controlling for family status, indicated that women and unemployed participants reported higher stress, anxiety, and depression levels than men and employed participants. Participants who experienced individual quarantine reported higher anxiety and depression. Furthermore, there was a significant interaction between gender, employment, and pandemic duration. The experience of individual quarantine intensified the stress, anxiety, and depression for both employed and unemployed women. Conversely, the quarantine intensified stress, anxiety, and depression only for unemployed men, whereas the quarantine did not affect stress, anxiety, and depression among employed men. Conclusions Employment is a critical factor regarding men's emotional state during such stressful situations as the COVID-19 pandemic. Furthermore, individual quarantine and long-term pandemics are associated with opposite outcomes regarding individual mental health. The individual quarantine is associated with increased anxiety and depression, while a long-term, continuous pandemic is associated with decreased stress.